Applying critical thinking and analysis in social work - Rogers, Michaela; Allen, Dan (Thousand Oaks, CA Sage, 2019)
This highly practical guidebook will help you develop the critical and analytical skills essential to your successful social work education and evidence-informed, reflective practice. Key features include: Theoretical break down and simplification of key theories How to avoid common pitfalls Activities to help you cement your learning Case studies applicable in practice.
Includes bibliographical references (pages 189-192) and index.
Keywords: Critical thinking; Social service -- Practice